Mother-young interactions and suckling behaviour in Blue Monkeys, Cercopithecus mitis - Nilsson, Jenny (SLU/Dept. of Animal Environment and Health (until 231231), 2008)
The infant's first months are of vital importance for establishing relations with the mother as well as with other group members. It is also a period of learning. As a part of a larger study of the blue monkey, Cercopithecus mitis stuhlmanni, my study focuses on interactions between mother and offspring and suckling behaviour.